Masses of Single, Double, and Triple Heavy Baryons in the Hyper-Central Quark Model by Using GF-AEIM - M. Abu-shady; H. M. Fath-Allah (Advances in High Energy Physics)
By using the generalized fractional analytical iteration method (GF-AEIM), the single, the double, and the triple heavy baryons masses are calculated in the hyper-central model in the two cases. In the first case, the potential is a combination of Coulombic potential, the linear confining potential, and the harmonic oscillator potential. In the second case, we add the hyperfine interaction. The energy eigenvalues and the baryonic wave function are obtained in the fractional forms. The present results are a good agreement with experimental data and are improved with other recent works.